Penyuluhan tentang Penanggulangan TB Paru dan Sanitasi Rumah Sehat Bagi Penderita TB Paru di Wilayah Kerja UPT Kesmas Sukawati Kabupaten Gianyar - I Made Bulda Mahayana (Poltekkes Kemenkes Denpasar, 2020)
Tuberculosis is an infectious disease transmitted by the bacterium Mycobacterium tuberculosis, a cause of death especially in developing countries throughout the world. The aim of community service is to find out how the knowledge of patients with pulmonary TB before and after counseling is given about prevention of pulmonary TB and sanitation in healthy homes in the work area of Sukawati II Public Health Unit, Gianyar Regency. The population in this community service is 33 TB sufferers. The method used in community service activities is interviews, measurement and observation. Evaluation of respondents' knowledge before (pre-test) and after (post-test) is given guidance and counseling on the prevention of pulmonary TB and sanitation of healthy homes. There was an increase in patient knowledge about the prevention of pulmonary TB before and after being given guidance and counseling, which amounted to 90.9%. There was an increase in the knowledge of pulmonary TB sufferers about sanitation in a healthy home before and after being given guidance and counseling, which was 87.9%. The state of healthy home sanitation, namely: lighting 18.2%, 21.2% humidity ventilation (84.8%), floors (87.9%), occupancy density (84.8%), kitchen (100%), latrines (100%), clean water facilities (100%), waste water facilities (100%) and waste management (100%) that meet the standards.Keywords: Coaching, Counseling, Healthy Home Sanitation